2004
DOI: 10.1191/1352458504ms1074oa
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-beta: the neutralizing antibody (NAb) titre predicts reversion to NAb negativity

Abstract: The NAb titre might support treatment decisions in patients with MS whose test results are positive for NAbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 20 publications
4
39
1
Order By: Relevance
“…Spontaneous seroreversion has been described in the presence of low BAbs/ NAbs titers [39,40]. In these patients, IFNb treatment does not need to be discontinued, but MxA should be regularly monitored.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Spontaneous seroreversion has been described in the presence of low BAbs/ NAbs titers [39,40]. In these patients, IFNb treatment does not need to be discontinued, but MxA should be regularly monitored.…”
Section: Discussionmentioning
confidence: 98%
“…Categorizing patients has different clinical implications: in patients with complete inhibition in MxA gene expression, NAbs and BAbs evaluations have to be performed, and IFNb treatment should be stopped in patients with high BAbs and NAbs titers, because they are associated with persistent sero-positivity [38,39]. Spontaneous seroreversion has been described in the presence of low BAbs/ NAbs titers [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study assessing the predictive value of NAb titres showed that the discrimination between those patients who remained NAb+ (non-reverters) and those who eventually reverted to NAb) status was best at 24 months of IFNb treatment. At that time, the magnitude of titres in non-reverters was significantly higher than that of reverters [45]. It has been suggested that NAb levels should be viewed as a continuum with regard to biological relevance.…”
Section: Detection Of Ifnb Binding Antibodiesmentioning
confidence: 97%
“…Approximately 30 % will revert to being NAB-negative over a period of several years. It appears that patients treated with IFN β-1b are more likely to revert to NAB-negative status [12] and, similarly, patients with a low NAB titre (< 75-100 NU/mL) are also more likely to revert to being NAB-negative than patients with higher NAB titres [13,14].…”
Section: The Issue Of Nab Persistencementioning
confidence: 86%